Nuclear and mtDNA genes suggest polyphyletic origin of species in the genus Euphyllidae - Luzon, Katrina S. (Animo Repository, 2022)
Veron (2000) devised a scheme to identify species in the family Euphyllidae that deviates from the traditional approach to coral taxonomy. For this family, soft tissue features were defined to be more crucial than corallum features in species identification. Polyp morphology, however, may not be sufficient to distinguish species particularly because the problem is further confounded by the occurrence of natural hybrids within this group. In this work, the phylogeny of the genus Euphyllia, the largest genus under the family Euphyllidae, was examined together with Nemenzophyllia turbida and Catalaphyllia jardinei. Nuclear and mitochondrial markers, particularly beta-tubulin and cytochrome oxidase 1 in Euphyllia species divide the genus into two distinct groups suggesting that the genus is polyphyletic. Neighbor-joining trees drawn with Kimura 2 parameter of 500 replicates clusters Euphyllia paradivisa and Euphyllia glabrescens together and separate from Euphyllia paraancora, E.paraglabrescens, E.ancora, and E divisa. Nemenzophyllia turbida and Catalaphyllia jardinei individually separates from the two Euphyllia clusters and the outgroup Galaxeafascicularis. These results suggest other characters are needed to resolve the species, at least, of Euphyllia and that revision of the family may be required.